Facile Synthesis of Enzyme-Embedded Metal–Organic Frameworks for Size-Selective Biocatalysis in Organic Solvent - Wang, Yangxin; Zhang, Ningning; Tan, Deming; Qi, Zhenhui; Wu, Changzhu (Frontiers in Bioengineering and Biotechnology, 2020)
In situ immobilization of enzyme into metal-organic frameworks (MOFs) is performed through a one-step and facile method. Candida Antarctica lipase B (CalB) is directly embedded in zeolitic imidazolate framework (ZIF-8) by simply mixing an aqueous solution of 2-methylimidazole and zinc nitrate hexahydrate (Zn(NO3)2•6H2O) containing CalB at room temperature. Due to the intrinsic micropores of ZIF-8, the obtained CalB@ZIF composite is successfully applied in size-selective transesterification reaction in organic solvent. CalB@ZIF not only shows much higher catalytic activity but also exhibits higher thermal stability than free CalB. Besides, the robust ZIF-8 shell also offers the hybrid composites excellent reusability.